Reproductive toxicity in male rats induced by chronic arsenic exposure involves hormonal and structural changes - Syed Zahid Mahboob; Sarwat Jahan; Hussain Badshah; Razia Virk; Mehwish David; Riffat Bano; Jawaher Alzahrani; Muhammad Ayub; Azizullah Azizullah; Moona Nazish; Asif Kamal; Kamran Ullah; et al. (Scientific Reports)
Abstract The current research focused on the chronic effect of arsenic (As3+, As III) on the reproductive system in male rats. Fifty male rats (190 ± 10 g) were separated into five groups to assess Arsenic induced physiological, hormonal and histopathological impairments. Following the dissection, blood, vital organs, accessory reproductive, testicular and hypothalamic tissues were obtained. Blood plasma was isolated and preserved for determining oxidative stress and performing hormonal analysis, while epididymis was used for sperm parameters assessment, and testis were subjected to histological analysis. The results revealed a significant decrease in percent sperm motility, sperm viability, and daily sperm production rate in high-dose treatment groups (25 and 50 mg/L). The concentrations of catalase, superoxide dismutase, and peroxidase were found to be significantly reduced. At the same time, a remarkable increase in reactive oxygen species (ROS) and thiobarbituric acid reactive species (TBARs) and was evident in a dose-dependent manner. Similarly, significantly low amounts of plasma testosterone, follicle-stimulating hormones (FSH), and luteinizing hormone (LH) were noted among treatment groups after exposure to arsenic. Histopathological findings showed remarkable multiple degenerations in seminiferous tubules including tubular atrophy, Leydig cells hypoplasia, proliferative marginal neoplasia, severe necrosis and acute germ cell aplasia leading to Sertoli cell-only syndrome. Fluorescent immune-cyto-chemical data confirmed a dose-proportional lowered quantitative expression in the number of gonadotrophins releasing hormone (GnRH) like immunoreactive (IR) neurons. Analysis of the comet assay revealed intensified nuclear denaturation and sperm DNA fragmentation in As3+ treated groups vs. the control. “Arsenic exposure induces oxidative stress, disrupts hormonal balance, impairs spermatogenesis, and causes testicular damage and DNA fragmentation, ultimately leading to reduced male fertility.”